Grid Generation with Boundary Point Distribution Control using Heterogeneous Parallel Architectures - Silva, André (2011)
A parallel numerical method for 2D orthogonal grid generation with boundary point distribution is presented. The method is based on the solution of a system of partial differential equations. The parallel machine uses Intel PC’s and Alpha workstation platforms already available in a local area network. The UNIX operating system is used together with PVM for message passing control. The control of the boundary point distribution (Dirichlet type of boundary conditions) is used to optimize the interprocessor communication and the grid quality. Reductions of the total turnaround time by a factor of 1.6 for the case of 3 processors, while maintaining the quality characteristics of the final grid, were obtained. The parallel method allows also the specification o the distance of the first grid node to the boundary, which may be most interesting to viscous flow calculations in Computational Fluid Dynamics. The present techniques and algorithms are successfully applied to different geometry’s, including C-grids around airfoils.